Environmental friendly wall cladding - Nor Azman, Ahmad Danial (2024)
After the Second World War, the idea of industrialised building system (IBS) has received much attention in the devastated countries. Though, Malaysia did not suffer the impact of the war, the need to supply its population with affordable and quality houses has prompted the government to promote the use of IBS as an alternative to conventional building system. The objective of this paper is to document the experiences of Malaysia as well as other countries in the adoption of IBS. (W.A.Thanoon, Lee Wah Peng, Mohd Razali Abdul Kadir, Mohd Saleh Jaafar and Mohd Sapuan Salit, 2003). Basically, wall cladding are divided into two categories which are natural and unnatural wall cladding. The natural cladding will use the raw material such as fibre from plants like coconut fibre, cork, bamboo and wood. The importance of use this is to produce a healthier life, no radiation, no formaldehyde and the most important it is 100 %green environmental protection. Natural materials like this are often forgotten, but we must remember that they have many advantage. Thus, this study's methodology uses both experimental data collecting and document review as its data collection methods. These two techniques make it simple to identify the innovation project idea, which calls for the use of environmental wall cladding. Indirectly, it can provide a precise measurement of thermal conductivity by conducting an experiment and provide more knowledge while doing a document review online study project.